Insulin Resistance in Type 1 Diabetes Mellitus and Its Association with Patient’s Micro- and Macrovascular Complications, Sex Hormones, and Other Clinical Data - Šimonienė, Diana (Diabetes Ther, 2019)
INTRODUCTION: The main objective of this research was to evaluate the association of insulin resistance (IR) with micro- and macrovascular complications, sex hormones, and other clinical data. METHODS: Cross-sectional study of patients older than 18 years old with type 1 diabetes mellitus (T1DM) was performed. Participants filled in questionnaires about T1D, disease duration, smoking, glycemic control, chronic diabetes complications, and hypertension status. Data about chronic diabetic complications (neuropathy, retinopathy, and nephropathy) were collected from medical records. History of major cardiovascular events such as angina, myocardial infarction, and stroke were collected from medical records also. Laboratory tests including creatinine, cholesterol levels, testosterone (T), sex hormone-binding globulin (SHBG), estradiol levels, and albumin in 24-h urine sample were performed. IR was calculated using the following formula: estimated glucose disposal rate (eGDR) = 24.31 − [12.22 × waist-to-hip ratio (WHR)] − [3.29 ×  hypertension status (defined as 0 = no, 1 = yes)] − [0.57 × glycated hemoglobin (HbA1c)]. The data was considered statistically significant at p < 0.05. RESULTS: A total of 200 people (mean age 39.9 ± 12.1 years) with T1D were included in the study. Patients with T1D were analyzed according to eGDR levels stratified by tertiles. The cutoff value of eGDR which reflects IR was less than 6.4 mg kg(−1) min(−1). When eGDR was less than 6.4 mg kg(−1) min(−1), diabetes microvascular complications occurred significantly more often (p < 0.001); the cutoff of eGDR for cardiovascular disease (CVD) events was less than 2.34 mg kg(−1) min(−1). Lower eGDR, longer diabetes duration, and lower HbA1c significantly increased CVD outcomes risk. eGDR was also significantly lower in smokers (7.3 ± 2.5 vs. non-smokers 8.2 ± 2.6, p = 0.011), the obese (lean 8.25 ± 2.47 vs. obese 5.36 ± 2.74, p < 0.000), older patients (less than 50 years 8.0 ± 2.5 vs. more than 50 years 6.2 ± 2.8, p = 0.001), men (men 6.4 ± 2.4 vs. women 8.7 ± 2.2, p < 0.001), patients with long-standing diabetes (< 10 years 7.3 ± 2.6 vs. > 10 years 8.7 ± 2.3, p < 0.001), and chronic diabetes complications (diabetic retinopathy, diabetic nephropathy, diabetic neuropathy, p < 0.001), and patients with CVD (with CVD 5.5 ± 2.4 vs. no CVD 8.0 ± 2.4, p < 0.001). Patients with T1D and a family history of T2D were not susceptible to weight gain during intensive insulin treatment. Metabolic syndrome (MS) phenotype prevalence, including and dyslipidemia rate, were higher in the obese group than in normal weight, but a clear difference was not seen (p = 0.07). Positive linear correlation between men’s T and eGDR level was observed (r = 0.33, p = 0.04), i.e., men with higher testosterone level had better insulin sensitivity. Other parameters (like T in women, estrogens, SHBG) did not show any significant association with eGDR. CONCLUSIONS: According to stratified eGDR, IR was found for one-third of the current T1D population. Insulin resistant patients more frequently had microvascular complications and CVD events. Lower eGDR, longer diabetes duration, and lower HbA1c significantly increased CVD outcomes risk. IR was related to smoking, obesity, gender, age, and diabetes duration. Moreover, men’s testosterone had a positive correlation with IR in T1D. Finally, patients with T1D and a positive family history of T2D were not susceptible to weight gain, while MS metabolic phenotype prevalence tended to be higher in obese than in lean patients with T1D, with a tendency to significant difference.